Application of new methodologies in an industrial electronics engineering course : case study - Leão, Celina Pinto (2006)
This paper describes an experience of ‘blended learning solution’ in different areas of an engineering course at a Portuguese University. This arose from the current interest in innovation and the new trends in engineering education. The communication between teacher and student is becoming increasingly important in students’ learning process. The Internet makes this communication possible and web tools, such as multimedia and video, makes it a practical:proposition: when the personal contact is not feasble the Internet enables contact through e-mail and web tools, as animations, motivate students to study. The solution described is a mix of traditional learning practices and e-learning, a blended approach that was implemented in the Industrial Electronics Engineering graduated course at the University of Minho. Three subjects were selected: Numerical Methods (3rd year), Automation (4th year) and Process Control (4th year). Due to the characteristics of numerical methods subject, problems are usually solved by using computers and, as this new methodology computer-based, students readily adapt and are naturally motivated. Using the knowledge acquired by this experience with numerical methods, the same methodology was applied to Automation and Process Control. Along with web tools and Internet services used for information retrieval and learning repository, some animations related to the subjects were included as well as self-evaluation tests, to allow the student to reflect on his/her learning process in a specific subject. In Process Control, a management web page functionality was included. The implementation of this solution requires a better and more precise definition of the subject objectives and contents, and subsequent assessment. While initially increasing teacher workload it also facilitates students’ individual study. This new methodology has been well accepted by the students, making them more active, better motivated and more responsiblr fortheir learning process and progress.